2014
DOI: 10.1016/j.jbiosc.2014.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human papillomavirus 6b L1 virus-like particles isolated from silkworms using capillary zone electrophoresis

Abstract: Human papillomavirus 6b L1 virus-like particles (VLPs) were successfully expressed using Bombyx mori nucleopolyhedrovirus (BmNPV) bacmid expression system and rapidly purified using size exclusion chromatography after ultracentrifugation procedure and characterized by capillary zone electrophoresis (CZE). The average capillary electrophoresis migration time was 11 min with the relative standard deviation (RSD) of 0.3% of human papillomavirus 6b L1 VLPs. After this threefold fractionation, the CZE samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, two excellent reviews describe the possible conditions for the characterization of viruses in general [85,86]. Based on Kremser et al [85], methods to characterize rhinovirus subviral A particles and papillomavirus 6b L1 VLPs have been developed, using slightly alkaline borate buffers containing the tenside Thesit® [87,88]. Furthermore, two following recent articles are highly recommended for an overview of this field, even though they deal with adenoviruses, which are quite different to Coronaviridae [89,90].…”
Section: Electrophoresismentioning
confidence: 99%
“…However, two excellent reviews describe the possible conditions for the characterization of viruses in general [85,86]. Based on Kremser et al [85], methods to characterize rhinovirus subviral A particles and papillomavirus 6b L1 VLPs have been developed, using slightly alkaline borate buffers containing the tenside Thesit® [87,88]. Furthermore, two following recent articles are highly recommended for an overview of this field, even though they deal with adenoviruses, which are quite different to Coronaviridae [89,90].…”
Section: Electrophoresismentioning
confidence: 99%
“…CE analysis offers many advantages such as online monitoring, rapid detection, and low consumption of sample and reagents. CZE, the most popular CE for SLPPs analysis, has been regarded to be a potential option for the quality control of SLPPs in R&D of pharmaceuticals [49].…”
Section: Analytical Techniques For Rapid Characterization and Quantifmentioning
confidence: 99%
“…Consequently, non‐enveloped icosahedral viruses possess a global negative surface charge at pH higher than the isoelectric point contributing to proffer them an electrophoretic mobility . Exploiting this characteristic, it has been shown that capillary zone electrophoresis (CZE), a separative analytical technique based on the difference of the electrophoretic mobility of the analytes , can be applied in the separation, detection and quantification of viral, subviral and virus‐like particles in aqueous media . However, in practice, the CZE analysis of viruses is harder than of molecules, where uncontrolled viral particles aggregation and capillary wall adsorption responsible of irreproducible results having been often encountered .…”
Section: Introductionmentioning
confidence: 99%